Monetary policy and commodity price shocks - Silke Tober; Tobias Zimmermann (Intereconomics, 2009)
Against the background of the dramatic changes in the prices of oil and other raw materials in the recent past, this paper analyses the effects of commodity price shocks in a New Keynesian model. The focus is on the central bank's choice of inflation target and the degree of real wage rigidity. It turns out that using core inflation rather than headline inflation is the superior strategy. Targeting expected headline inflation, as practised by most central banks, is a viable practical alternative to the core inflation target.
Keywords: 330